Caffeine-containing energy drink improves physical performance of elite rugby players during a simulated match - Del Coso, J.; Ramirez, J. A.; Munoz, G.; Portillo, J.; Gonzalez-Millan, J.; Munoz, V.; Barbero-Alvarez, J. C.; Munoz-Guerra, J. (Applied Physiology, Nutrition, and Metabolism, 2013)
The purpose of this study was to investigate the effectiveness of a caffeine-containing energy drink in enhancing rugby players' physical performance during a simulated match. A second purpose was to determine the urinary caffeine excretion derived from the energy drink intake. In a randomized and counterbalanced order, 26 elite rugby players (mean ± SD for age and body mass, 25 ± 2 y and 93 ± 15 kg) played 2 simulated rugby games (2 × 30 min) 60 min after ingesting (i) 3 mg of caffeine per kilogram of body mass in the form of an energy drink (Fure, ProEnergetics) or (ii) the same drink without caffeine (placebo). During the matches, the individual running distance and the instantaneous speed were measured, and the number of running actions above 20 km/h (i.e., sprints) were determined, using global positioning system devices. The number of impacts above 5 g during the matches was determined by accelerometry. The ingestion of the energy drink, compared with the placebo, increased the total distance covered during the match (4749 ± 589 vs 5139 ± 475 m, p < 0.05), the running distance covered at more than 20 km/h (184 ± 38 vs 208 ± 38 m, p < 0.05), and the number of sprints (10 ± 7 vs 12 ± 7, p < 0.05). The ingestion of the energy drink also resulted in a greater overall number of impacts (481 ± 352 vs 641 ± 366, p < 0.05) and a higher postexercise urine caffeine concentration (0.1 ± 0.1 vs 2.4 ± 0.9 µg/mL, p < 0.05). The use of an energy drink with a caffeine dose equivalent to 3 mg/kg considerably enhanced the movement patterns of rugby players during a simulated match